Public Private Partnership A new hope from Union Budget 2019-20 - Mathur, Vinay (Indian Farming, 2019)
INDIAN agriculture has marked its presence at the global level. India ranks either first or second in terms of total production of rice, wheat, sugarcane, fruits and vegetables in the world. However despite this, there is fluctuation in growth of Indian agriculture. This signifies that, agriculture sector is important, nevertheless it still needs support. The sector needs huge fillip for multiple reasons, viz. productivity in all major crops have stagnated, need for significant improvement in agriculture infrastructure, land holdings continue to be fragmented, and risk mitigation options still needs to reach beneficiaries. Added to these are the new challenges attributable to climate change. The implication of these issues on agriculture is complex and would have to be dwelt with series of mitigation and adaptation measures. It is in this context, there is a need for newer approach to strengthen Indian agriculture, where the synergies of both the public sector and the private sector are harnessed for the benefit of farmers.